Mangrove distribution in the Arabian Gulf for the year 2017 - Hanan Almahasheer (PANGAEA, 2018)
Mangroves are the natural protectors of the coast, carbon sinks, and a nursery to many terrestrial as well as aquatic organisms. Different effects caused by natural forces together with anthropogenic factors have reduced mangrove cover on a global scale, yet little is known about the overall surface covered by mangroves in the Arabian Gulf. Therefore, the aim of this study was to examine their spatial coverage and distribution along the Gulf coastlines, using 25 satellite imagery recently acquired from Landsat 8 data for the year 2017. This study found about 165 km**2 of fragmented scattered mangroves, mostly intense in the United Arab Emirates, where plantation projects have likely played a significant role in increasing their cover over the years. Whereas mangrove in Kuwait is rare, areas like Bahrain, Qatar and Saudi Arabia remained stable with a slight increase. However, mangroves in Iran appear to suffer a decline throughout the years.
Supplement to: Almahasheer, H (2018): Spatial coverage of mangrove communities in the Arabian Gulf. Environmental Monitoring and Assessment, 190(2), 85, https://doi.org/10.1007/s10661-018-6472-2